VIDEO MAKING TASK TO DECREASE ANXIETY IN THE STUDENTS’ SPEAKING PERFORMANCE - Endang Setiyo Astuti; Indrawati Pusparini (Journey: Journal of English Language and Pedagogy, 2020)
Anxiety is one of the factors influencing students’ speaking performance in the classroom. A video making task is an alternative strategy that can decrease anxiety besides it provides a positive influence on students’ self-assessment of speaking task. Hence, the objective of this study was to describe how video making task could decrease students’ anxiety in speaking class. This study used a descriptive qualitative method in which the data source was the students’ performance in video to require the task of procedure text presentation in speaking class. The data were collected by using observation and interview. And the result of the observation of the video showed that most of the students seemed less anxious and more relaxed in explaining the assigned materials. In the interview, the students also said that they felt more confident in presenting the task. In conlusion, the video making task could decrease students’ anxiety in students’ speaking performance